Role of probiotic in modulating immune response and prevention of constipation in critically ill patients: A randomized, double - blind, placebo - controlled trial / Fauziah Ahmad - Fauziah, Ahmad (2016)
Objectives : To assess the efficacy of pro biotic in 1) the probiotic effect in enhancing immune responce 2) prevention of constipation in critically ill patient. Design : A single centre, randomised, double blind, placebo controlled tudy that was conducted in the Intensive Care Unit, Universitiy Malaya Medical Centre between Jun 2016 to December 2016. A total of 36 patients who required mechanical ventilation and enteral nutritional feeding for atleast 3 days were randomised into two group : the intenvention group who received Hexbio, a probiotic preparation or the control group who received placebo. The patient were monitored for 5 consecutive days. Blood sample taken on 1,3,5 days of intervention,min reflo reading with total usage of intravenous insulin, timing for first bowel movement, stool frequency and consistency were recorded using King's stool chart. Result: Primary outcome : Serum analysis for IL-6, IL-10 and hemeoxygenase still in progress. Therefore unable to modulate the outcomes. Secondary outcomes: The intervention group showed shorter time for first bowel opening of 3.2 days compared with 4.6 days in placebo group (p=0.03). It is also showed higher mean frequency 3.75 times perday compared with 0.35 times perday ( p=0.09). Beside that, they also presented with lower gastric aspirates with p value 0.0003. Other parameter showed indirect beneficial effect of probiotic in reducing morbidity in critically ill by reduce lenght of ICU stay, reduce number of days required ventilator support and better min blood sugar level. Conclusion : Probiotics could reduce inflammation in critically ill-patients and might be considered as an adjunctive therapy in the treatment if critically ill-patients as it help in reduce morbidity . Probiotics also have beneficial effect in preventing contipations as statiscally showed significant difference in first bowel opening and reduced mean gastric contents daily. Other that that, probitotic promote antioxidant effect which suqsequently help in ontrollinu blood sugar level in critical ill patients.